Manufacturing method of green energy-saving nitrided plastic sintered filter plate

Through the ion nitriding, sintering, liquid nitrogen freezing and high-purity nitrogen nitriding treatment on the surface of liquid ammonia, a dense nitride layer is formed, which solves the problem of the short service life of the existing plastic sintered filter plate in high temperature and corrosion environments, and achieves a high-performance and long-life nitrided plastic sintered filter plate.

CN119793075AActive Publication Date: 2025-04-11SHANGHAI SUPERHIGH ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411631235.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-31
Filing Date
2024-11-15
Publication Date
2025-04-11
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing plastic sintered filter plates have short service life in high temperature and corrosive environments, and are difficult to meet the needs of the new energy industry and the additive industry for high purity extraction and separation.

Method used

Ultra-high molecular weight polyethylene is treated with ion nitriding of liquid ammonia to form a hardened layer, followed by sintering molding and liquid nitrogen freezing treatment, and finally pulsed plasma nitriding is used with high-purity nitrogen to form a dense nitride layer.

Benefits of technology

It significantly improves the wear resistance, high temperature and corrosion resistance of nitrided plastic sintered filter plates, extends the service life, and reduces energy consumption and filter resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793075A_ABST
    Figure CN119793075A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing method of a green energy-saving nitrided plastic sintered filter plate, and belongs to the technical field of high polymer materials. The method comprises the following steps: firstly, carrying out primary nitridation by using liquid ammonia, permeating nitrogen atoms into a surface layer of an ultra-high molecular weight polyethylene material through surface ion nitridation treatment, and combining the nitrogen atoms with carbon atoms in the material to form a nitride, so that a hard nitride layer is formed on the surface of the material; after sintering molding and liquid nitrogen treatment, high-purity nitrogen is used for secondary nitriding, a nitriding layer can be more compact and uniform, a pulsed power supply is used for carrying out plasma nitriding treatment on a material, so that nitrogen ions further permeate into the material and are combined with a nitride layer formed by primary nitriding, and a deeper nitride layer is formed; the performance and the service life of the material are further improved; the burr fine particle material screened out in the nitriding process can be reused in the production material of the ultra-high molecular wear-resisting plate, so that the method is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a method for manufacturing a green and energy-saving nitrided plastic sintered filter plate. Background Art

[0002] The plastic sintered filter plates and filter cartridges currently in use are the main filter elements for air pollution control and are playing a leading role in the field of ultra-low emissions in the dust removal of the steel, smelting and automotive industries. In recent years, with the continuous advancement of new quality productivity and high-quality development, the development of high-purity extraction and separation technology for lithium batteries and hydrogen energy storage materials in the new energy industry, as well as laser smoke fine filtration and inert gas push in the additive industry require high-quality, high-precision personalized filter materials. This has put forward new requirements for technicians in the plastic sintered filter material industry. The development of a nitrided plastic sintered filter plate with good wear resistance, high temperature resistance and corrosion resistance to meet the needs of the development of new quality productivity is also a problem that needs to be solved in the field of environmental protection materials today.

[0003] Therefore, scientific researchers in the plastic sintered filter material industry are committed to developing a nitrided plastic sintered filter plate to solve the wear-resistant, high-performance plastic sintered filter material in high-quality development, to solve the technical problems in high-purity extraction and laser smoke fine filtration operations, so that the nitrided plastic sintered filter plate can serve the industry needs for high-quality development of new quality productivity.

[0004] The present invention provides a method for manufacturing a green and energy-saving nitrided plastic sintered filter plate, which can make the surface of the plastic sintered filter material waterproof, oil-proof, and corrosion-resistant, so that it can work stably in various acid, alkali, and arc smoke environments, and at the same time can extend the service life of the nitrided plastic sintered filter plate. Summary of the invention

[0005] The purpose of the present invention is to provide a method for manufacturing a green and energy-saving nitrided plastic sintered filter plate, which has the characteristics of long service life of the manufactured nitrided plastic sintered filter plate.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for manufacturing a green and energy-saving nitride plastic sintered filter plate. The specific process of the method for manufacturing a nitride plastic sintered filter plate is as follows:

[0008] S1: ultra-high molecular weight polyethylene is placed in a sealed reactor, and a stirring paddle is driven to rotate in the forward direction. Liquid ammonia is introduced into the reactor while the rotation is performed, and a DC power supply is introduced while the liquid ammonia is introduced, and the pressure is increased to 5MPa. The ultra-high molecular weight polyethylene is used as the cathode for surface ion nitridation treatment. The stirring paddle is continuously stirred in the reactor, and the temperature is controlled at 30°C while stirring to obtain material A, in which the mass ratio of ultra-high molecular weight polyethylene to liquid ammonia is 50:1;

[0009] S2: The ammonia generated in the reaction is absorbed by the VOC purification system, the material A is screened, and the material A with a particle size of 100 to 150 mesh is selected for sintering to obtain material B;

[0010] S3: placing material B into liquid nitrogen for freezing treatment at a temperature of -196°C for 2 to 3 hours, and then rapidly heating it to room temperature under a nitrogen atmosphere to obtain material C;

[0011] S4: Material C is transferred to a closed reactor, and ultra-high purity nitrogen is introduced at a flow rate of 5 L / min. After the temperature is raised from room temperature to 180°C, a pulse power supply is used to perform plasma nitriding treatment on material C. The pulse frequency is 2000 Hz, the voltage is 1000 V, and the current is 100 A. At the same time, the pressure is increased to 1.5 MPa. The reaction time is 6 hours. After the reaction is completed, it is naturally cooled to room temperature and allowed to stand for 6 hours to obtain the nitrided plastic sintered filter plate.

[0012] Furthermore, the molecular weight of the ultra-high molecular weight polyethylene in S1 is 5 million.

[0013] Furthermore, the particle size of the ultra-high molecular weight polyethylene in S1 is 100-150 meshes.

[0014] Furthermore, the parameter of the DC power supply in S1 is a voltage of 600V.

[0015] Furthermore, the stirring rate in S1 is 200 r / min.

[0016] Furthermore, the sintering temperature in S2 is 225° C., and the sintering time is 3 hours.

[0017] Furthermore, the heating rate in S3 is 10°C / min.

[0018] Furthermore, the concentration of the ultra-high purity nitrogen in S4 is 99.9999%.

[0019] Furthermore, the heating rate in S4 is 3°C / min.

[0020] Furthermore, the S4 is naturally cooled to room temperature in an ultra-high purity nitrogen atmosphere.

[0021] When selecting materials for ordinary plastic-fired boards, people only pay attention to the molecular weight of ultra-high molecular weight polyethylene materials (such as 3.5 million units, 4.5 million units and 6 million units), and ignore the selection of ultra-high molecular weight polyethylene particle size. Moreover, they do not consider the roundness of the granular material (in fact, the particle surface of these materials is irregular). The purchased raw materials are directly selected according to the label, resulting in materials of different sizes of particles being cross-concentrated together, causing the channels between the gaps to be of different sizes, affecting the smoothness of the channels and restricting the efficiency of the opening rate. When used specifically, it will greatly increase the resistance loss.

[0022] In the present invention, liquid ammonia is first used to perform a nitridation on ultra-high molecular weight polyethylene, and the surface properties of ultra-high molecular weight polyethylene are improved by surface ion nitridation treatment, and its wear resistance is improved. Liquid ammonia nitridation can form a nitrogen-rich hardened layer on the surface of the material, significantly improve the surface hardness of the material, and make it more wear-resistant. Liquid ammonia is introduced into the reactor, and a DC power supply with a voltage of 600V is introduced. The DC power supply of this strength can provide sufficient electric field strength to promote the migration of nitrogen ions to the polyethylene surface. At the same time, the pressure in the reactor is increased to 5MPa, and the temperature is controlled at 30°C. At this pressure and temperature, the liquid ammonia is in a gas-liquid coexistence state. Under this reaction condition, it is more conducive to the formation of nitrogen ions; the plastic sintered plate is used as the cathode and placed in the reactor. Under the action of the electric field, the nitrogen ions in the liquid ammonia will be attracted and move to the cathode. When the nitrogen ions contact the surface of the ultra-high molecular weight polyethylene, a chemical reaction will occur. These reactions include the combination of nitrogen elements with carbon atoms on the surface of polyethylene to form a nitride layer. This layer of nitride has excellent hardness and wear resistance, and can significantly improve the surface properties of the material. During the entire reaction process, the temperature in the reactor needs to be controlled at 30°C. This temperature range helps promote the chemical reaction while avoiding excessively high temperatures that may cause material decomposition or burning.

[0023] After the first nitridation is completed, the ultra-high molecular weight polyethylene is heated to a heat deformation temperature of 225°C, which is higher than the melting point (130-136°C). At this temperature, the ultra-high molecular weight polyethylene with a particle size of 100-150 mesh is sintered and formed. Through sintering, the gaps between the particles inside the ultra-high molecular weight polyethylene material can be reduced, and the disordered gaps can be turned into ordered gaps, thereby improving the density of the material. This helps to improve the mechanical properties and wear resistance of the material; sintering can form a layer of nitride with higher hardness on the surface of the ultra-high molecular weight polyethylene material, thereby improving the hardness and wear resistance of the material; sintering can improve the surface finish and precision of the ultra-high molecular weight polyethylene material and reduce the friction coefficient.

[0024] Liquid nitrogen treatment can quickly reduce the temperature of material B to -196℃, which will cause changes in the molecular chains and crystal structure inside the material. During the freezing process, the movement of the molecular chains slows down or even stops, which helps to form a more stable structure; after freezing, when the material is quickly heated to room temperature in a nitrogen atmosphere, the molecular chains will regain their mobility, but due to the influence of the previous freezing treatment, they will rearrange in a more orderly and stable way, thereby optimizing the microstructure of the material; in addition, liquid nitrogen treatment can effectively eliminate the residual stress generated during the processing process through the rapid changes of freezing and heating; stress elimination helps to improve the toughness and impact resistance of the material, providing a more stable and uniform foundation for the subsequent nitriding process.

[0025] The surface and internal microstructure of material C treated with liquid nitrogen are optimized, which makes the subsequent nitrogen nitriding process easier. During the nitrogen nitriding process, nitrogen atoms need to penetrate into the material and combine with atoms in the material to form a nitrided layer. Liquid nitrogen treatment optimizes the microstructure of the material, providing more channels and opportunities for the penetration of nitrogen atoms, and liquid nitrogen treatment can also improve the material's adsorption capacity for nitrogen, thereby further promoting the nitriding process.

[0026] After the liquid nitrogen treatment, material C is transferred to a sealed reactor to ensure the closed reaction environment. Ultra-high purity nitrogen (concentration of 99.9999%) is introduced at a flow rate of 5L / min to provide sufficient nitrogen source and remove other gases in the reactor to ensure the purity of the reaction environment.

[0027] The temperature is raised from room temperature to 180°C at a rate of 3°C / min. This step is to allow material C to reach the temperature required for the nitriding reaction. During the heating process, ultra-high purity nitrogen is continuously introduced to ensure the stability of the reaction environment. When the temperature in the reactor reaches 180°C, a pulse power supply is used to perform plasma nitriding treatment on material C.

[0028] The pulse frequency is 2000Hz, the voltage is 1000V, and the current is 100A. These parameters act together on the surface of material C to generate high-energy plasma. Under the action of high-energy plasma, ultra-high purity nitrogen is decomposed into primary nitrogen atoms or nitrogen ions. The primary nitrogen atoms or nitrogen ions react chemically with the carbon and hydrogen elements on the surface of material C to further generate a nitride layer. This reaction process is carried out under a pressure of 1.5MPa to ensure sufficient contact and reaction between nitrogen and the surface of material C. The reaction time is 6h to ensure the full formation and stability of the nitride layer. After the reaction is completed, it is naturally cooled to room temperature in an ultra-high purity nitrogen atmosphere. This step is to prevent the nitride layer from cracking or falling off during the cooling process.

[0029] The present invention uses high-purity nitrogen with a concentration of 99.9999% to perform secondary nitriding on the sintered material, which can further deepen the depth of the nitrided layer and improve the nitriding effect; the two nitriding processes can ensure the uniformity of the nitrided layer on the surface of the ultra-high molecular weight polyethylene material and avoid the situation of insufficient or excessive local nitriding; through the two nitriding processes, the hardness, wear resistance and corrosion resistance of the ultra-high molecular weight polyethylene material can be further improved.

[0030] By adding ammonia to the polyethylene raw material particles for fusion reaction, the ammonia is decomposed to produce active nitrogen atoms, thereby forming the nitriding modification of the polyethylene material, solving the problem of removing the surface defects of the material particles, increasing the bonding degree between the particles, maintaining the regularity of the micropore morphology and structure, and reducing the resistance loss of the filter plate. Then, through the ultra-high purity nitrogen active reaction on the molded substrate, the surface hardness and wear resistance of the plastic-sintered filter plate are innovatively increased, so that it can resist various surface damage and wear, and the surface adsorption capacity is enhanced, so that the surface of the plastic-sintered filter material plays the role of waterproof, oil-proof, and corrosion-resistant, so that it can work stably in various acid, alkali, arc flue gas environments, and at the same time, it can extend the service life of the nitrided plastic-sintered filter plate. In addition, the burr fine particles screened out in the nitriding process can be reused in the production of ultra-high molecular wear-resistant plates to improve the temperature resistance and wear resistance of the wear-resistant plates, making them green and environmentally friendly; on the other hand, due to the specification of the aperture, the channel standard of the micropores is unified, which meets the constant low wind resistance operation, reduces energy consumption, improves dust removal efficiency, and meets the requirements of energy saving.

[0031] Beneficial effects of the present invention:

[0032] The present invention first uses liquid ammonia to perform a nitridation, and improves the surface properties of ultra-high molecular weight polyethylene through surface ion nitridation treatment. These nitrogen atoms penetrate into the surface layer of the ultra-high molecular weight polyethylene material and combine with carbon atoms in the material to form nitrides, thereby forming a hard nitride layer on the surface of the material; after sintering and liquid nitrogen treatment, high-purity nitrogen is used for secondary nitridation, which can make the nitride layer more dense and uniform, and a pulse power supply is used to perform plasma nitriding treatment on the material so that nitrogen ions can further penetrate into the interior of the material and combine with the nitride layer formed by the initial nitridation to form a deeper nitride layer, thereby further improving the performance and service life of the material; in the present invention, the burr fine particles screened out in the nitridation process can be reused in the production materials of ultra-high molecular wear-resistant plates, which is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0034] Figure 1 Comparison chart of particle structure of nitride plastic sintered filter plate materials. DETAILED DESCRIPTION

[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.

[0036] Example 1

[0037] S1: Ultra-high molecular weight polyethylene with a molecular weight of 5 million is placed in a sealed reactor, the particle size of the ultra-high molecular weight polyethylene is 100-150 meshes, the stirring paddle is driven to rotate in the forward direction, the stirring rate is 200r / min, and liquid ammonia is introduced into the reactor while rotating, and a DC power supply with a voltage of 600V is introduced while the liquid ammonia is introduced, and the voltage is increased to 5MPa, and the surface ion nitridation treatment is performed with the ultra-high molecular weight polyethylene as the cathode, and the stirring paddle is continuously stirred in the reactor, and the temperature is controlled at 30°C while stirring, to obtain material A, wherein the mass ratio of the added ultra-high molecular weight polyethylene to the liquid ammonia is 50:1;

[0038] S2: The ammonia generated in the reaction is absorbed by the VOC purification system, the material A is screened, and the material A with a particle size of 100-150 mesh is selected for sintering. The sintering temperature is 225°C and the sintering time is 3 hours to obtain the material B;

[0039] S3: Material B is placed in liquid nitrogen for freezing treatment at a temperature of -196°C for 2 to 3 hours. After freezing, the material is rapidly heated to room temperature in a nitrogen atmosphere at a heating rate of 10°C / min to obtain material C;

[0040] S4: Material C is transferred to a closed reactor, and ultra-high purity nitrogen is introduced at a flow rate of 5 L / min, the concentration of ultra-high purity nitrogen is 99.9999%, and the temperature is raised from room temperature to 180°C at a heating rate of 3°C / min. A pulse power supply is used to perform plasma nitriding treatment on material C, with a pulse frequency of 2000 Hz, a voltage of 1000 V, and a current of 100 A. At the same time, the pressure is increased to 1.5 MPa, and the reaction time is 6 hours. After the reaction is completed, it is naturally cooled to room temperature in an ultra-high purity nitrogen atmosphere and allowed to stand for 6 hours to obtain the nitrided plastic sintered filter plate.

[0041] Comparative Example 1

[0042] S1: Ultra-high molecular weight polyethylene with a molecular weight of 5 million is placed in a sealed reactor, the particle size of the ultra-high molecular weight polyethylene is 100-150 meshes, the stirring paddle is driven to rotate in the forward direction, the stirring rate is 200r / min, and liquid ammonia is introduced into the reactor while rotating, and a DC power supply with a voltage of 600V is introduced while the liquid ammonia is introduced, and the voltage is increased to 5MPa, and the surface ion nitridation treatment is performed with the ultra-high molecular weight polyethylene as the cathode, and the stirring paddle is continuously stirred in the reactor, and the temperature is controlled at 30°C while stirring, to obtain material A, wherein the mass ratio of the added ultra-high molecular weight polyethylene to the liquid ammonia is 50:1;

[0043] S2: The ammonia generated in the reaction is absorbed by a VOC purification system, the material A is screened, and the material A with a particle size of 100 to 150 mesh is selected for sintering. The sintering temperature is 225° C. and the sintering time is 3 hours to obtain the nitride plastic sintered filter plate.

[0044] Comparative Example 2

[0045] S1: Sintering ultra-high molecular weight polyethylene with a molecular weight of 5 million and a particle size of 100-150 mesh at a sintering temperature of 225° C. for 3 hours to obtain material B;

[0046] S2: Material B is placed in liquid nitrogen for freezing treatment at a temperature of -196°C for 2 to 3 hours. After freezing, the material is rapidly heated to room temperature in a nitrogen atmosphere at a heating rate of 10°C / min to obtain material C;

[0047] S3: Material C is transferred to a closed reactor, and ultra-high purity nitrogen is introduced at a flow rate of 5 L / min, the concentration of ultra-high purity nitrogen is 99.9999%, and the temperature is raised from room temperature to 180°C at a heating rate of 3°C / min. A pulse power supply is used to perform plasma nitriding treatment on material C, with a pulse frequency of 2000 Hz, a voltage of 1000 V, and a current of 100 A. At the same time, the pressure is increased to 1.5 MPa, and the reaction time is 6 hours. After the reaction is completed, it is naturally cooled to room temperature in an ultra-high purity nitrogen atmosphere and allowed to stand for 6 hours to obtain the nitrided plastic sintered filter plate.

[0048] Comparative Example 3

[0049] The specific process of the method for making the nitride plastic sintered filter plate is as follows:

[0050] S1: Ultra-high molecular weight polyethylene with a molecular weight of 5 million is placed in a sealed reactor, the particle size of the ultra-high molecular weight polyethylene is 100-150 meshes, the stirring paddle is driven to rotate in the forward direction, the stirring rate is 200r / min, and liquid ammonia is introduced into the reactor while rotating, and a DC power supply with a voltage of 600V is introduced while the liquid ammonia is introduced, and the voltage is increased to 5MPa, and the surface ion nitridation treatment is performed with the ultra-high molecular weight polyethylene as the cathode, and the stirring paddle is continuously stirred in the reactor, and the temperature is controlled at 30°C while stirring, to obtain material A, wherein the mass ratio of the added ultra-high molecular weight polyethylene to the liquid ammonia is 50:1;

[0051] S2: The ammonia generated in the reaction is absorbed by the VOC purification system, the material A is screened, and the material A with a particle size of 100-150 mesh is selected for sintering. The sintering temperature is 225°C and the sintering time is 3 hours to obtain the material B;

[0052] S3: Material B is transferred to a closed reactor, and ultra-high purity nitrogen is introduced at a flow rate of 5 L / min. The concentration of ultra-high purity nitrogen is 99.9999%. After heating from room temperature to 180°C, the heating rate is 3°C / min. Material C is plasma nitrided using a pulse power supply with a pulse frequency of 2000 Hz, a voltage of 1000 V, and a current of 100 A. At the same time, the pressure is increased to 1.5 MPa, and the reaction time is 6 hours. After the reaction is completed, it is naturally cooled to room temperature in an ultra-high purity nitrogen atmosphere and allowed to stand for 6 hours to obtain the nitrided plastic sintered filter plate.

[0053] The wind resistance performance of the embodiments and comparative examples was tested according to the group standard T / XCLC0001-2018 "Plastic Sintered Filter Plate for Dust Collector". The test sample size was 1500*564*80mm. A certain flow of wind was passed from one side of the nitride plastic sintered filter plate to the other side. The pressure on both sides was measured respectively, and the pressure difference was calculated. The greater the pressure difference, the greater the resistance of the filter plate. The test results are summarized in the following table.

[0054] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Flow rate (m 3 / h)]]> 500 500 500 500 Outlet(Pa) 541 658 653 605 Inlet (Pa) 65 65 65 65 Pressure difference (Pa) 476 593 588 540

[0055] It can be seen from the experimental data that the embodiment has the best ventilation performance, which shows that the plastic-sintered filter plate after secondary nitridation can maintain the regularity of the micropore morphology and structure, thereby reducing the resistance loss of the filter plate.

[0056] The wear resistance of the embodiment and comparative examples 1 to 3 was tested. The sample size was 120*100*80mm. The JMIV abrasion tester was used. The rotating friction rubber wheel method was used. The wear resistance of the present invention was measured by the average value of mass loss (weight loss method) after 100 grinding revolutions. The load was 10N, the rotation speed was 80r / min, the test temperature was 25°C, the relative humidity was 50%, and the mass was tested to an accuracy of 0.01mg. The average value of 3 measurements was taken as the result. The test results are summarized in the following table.

[0057] 100 revolutions mass loss / mg Example 1 35.88 Comparative Example 1 41.52 Comparative Example 2 43.65 Comparative Example 3 38.86

[0058] It can be seen from the experimental data that the embodiment has the best wear resistance, which means that the plastic-sintered filter plate treated with liquid nitrogen and secondary nitrided has better wear resistance and longer service life.

[0059] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for manufacturing a green and energy-saving nitride plastic sintered filter plate, characterized in that: The specific process of the method for making the nitride plastic sintered filter plate is as follows: S1: ultra-high molecular weight polyethylene is placed in a sealed reactor, and a stirring paddle is driven to rotate in the forward direction. Liquid ammonia is introduced into the reactor while the rotation is performed, and a DC power supply is introduced while the liquid ammonia is introduced, and the pressure is increased to 5MPa. The ultra-high molecular weight polyethylene is used as the cathode for surface ion nitridation treatment. The stirring paddle is continuously stirred in the reactor, and the temperature is controlled at 30°C while stirring to obtain material A, in which the mass ratio of ultra-high molecular weight polyethylene to liquid ammonia is 50:1; S2: The ammonia generated in the reaction is absorbed by the VOC purification system, the material A is screened, and the material A with a particle size of 100 to 150 mesh is selected for sintering to obtain material B; S3: placing material B into liquid nitrogen for freezing treatment at a temperature of -196°C for 2 to 3 hours, and then rapidly heating it to room temperature under a nitrogen atmosphere to obtain material C; S4: Material C is transferred to a closed reactor, and ultra-high purity nitrogen is introduced at a flow rate of 5L / min. After the temperature is raised from room temperature to 180°C, a pulse power supply is used to perform plasma nitriding treatment on material C, with a pulse frequency of 2000Hz, a voltage of 1000V, and a current of 100A. At the same time, the pressure is increased to 1.5MPa, and the reaction time is 6 to 8h. After the reaction is completed, it is naturally cooled to room temperature and allowed to stand for 6h to obtain the nitrided plastic sintered filter plate.

2. The method for manufacturing a green and energy-saving nitrided plastic sintered filter plate according to claim 1, characterized in that: The molecular weight of the ultra-high molecular weight polyethylene in S1 is 5 million.

3. The method for manufacturing a green and energy-saving nitrided plastic sintered filter plate according to claim 1, characterized in that: The particle size of the ultra-high molecular weight polyethylene in S1 is 100-150 meshes.

4. The method for manufacturing a green and energy-saving nitrided plastic sintered filter plate according to claim 1, characterized in that: The parameter of the DC power supply in S1 is a voltage of 600V.

5. The method for manufacturing a green and energy-saving nitride plastic sintered filter plate according to claim 1, characterized in that: The stirring rate in S1 is 200 r / min.

6. The method for manufacturing a green and energy-saving nitride plastic sintered filter plate according to claim 1, characterized in that: The sintering temperature in S2 is 225° C. and the sintering time is 3 h.

7. The method for manufacturing a green and energy-saving nitrided plastic sintered filter plate according to claim 1, characterized in that: The heating rate in S3 is 10°C / min.

8. The method for manufacturing a green and energy-saving nitride plastic sintered filter plate according to claim 1, characterized in that: The concentration of the ultra-high purity nitrogen in the S4 is 99.9999%.

9. The method for manufacturing a green and energy-saving nitrided plastic sintered filter plate according to claim 1, characterized in that: The heating rate in S4 is 3°C / min.

10. The method for manufacturing a green and energy-saving nitrided plastic sintered filter plate according to claim 1, characterized in that: The S4 is naturally cooled to room temperature in an ultra-high purity nitrogen atmosphere.

Citation Information

Patent Citations

  • Preparation method of silicon nitride fiber filtration material

    CN105503200A

  • Manufacturing method of one-step formed super-length plastic-sintered plate

    CN110789144A

  • Nitrogen-doped vanadium oxide nano electrode material for lithium ion battery and preparation process of nitrogen-doped vanadium oxide nano electrode material

    CN115974154A

  • Manufacturing method of green energy-saving nitrided plastic sintered filter plate

    CN118558055A

  • Method and apparatus for nitriding by post-plasma

    KR1020060072523A

Cited By

  • Clean zero-carbon filter element and preparation method thereof

    CN121868982A